Herbicide Application Techniques for Woody Plant Control - Jason Ferrell; Ken Langeland; Brent Sellers (EDIS, 2019)
The progression of trees and other woody plants into pastures, fencerows, ditch banks, rights-of-way and other areas is a common occurrence. These woody species can be particularly troublesome and require control since they will compromise fence intregrity, impede canal drainage, interfere with transmission of electricity, and some species (such as cherry trees) are highly poisonous to livestock. The aim of this publication is to detail the techniques for the removal of woody plants. This document is SS-AGR-260, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date January 2006. Reviewed November 2006.